Mind Mapping in CLIL: How It Facilitates Students’ Reading Comprehension - Evi Puspitasari (Journal of English Education and Teaching, 2020)
In Content and Language Integrated Learning (CLIL) where students are exposed with texts in a language that they are still learning, a mind map could be one of significant alternatives to gain students’ reading comprehension. This exploratory research discuses six EFL students’ voices about how mind map can be an instrument to comprehend English texts they read. In gaining the data, thirty-seven students who enrolled a theory-based subject in forth semester were assigned to write a reflective essay about mind map tasks and six forth semester students were interviewed to get the main data. Students’ portfolio of mind map assignment with teacher feedback was employed to triangulate the interview data. The results show that thirty-seven students agreed that mind map assisted them to comprehend English texts, yet the process was a bit complicated for them. All process that students passed through in making mind map contributed to reach L2 reading comprehension in CLIL classroom. Conclusion and recommendation are also discussed in this article.